2020
DOI: 10.1016/j.jsb.2020.107494
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the stability and substrate specificity of the E. coli aerobic β-oxidation trifunctional enzyme complex

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 55 publications
(64 reference statements)
0
13
0
Order By: Relevance
“…We are only aware of one other case of a Zn‐finger protein involved in a catalytic process, namely in adenylate kinase from Bacillus stearothermophilus (https://doi.org/10.2210/pdb1ZIN/pdb) where it provides a structural lid for the active site [35]. Another example where protein assembly is required to attain thiolase activity was reported for a trifunctional β‐oxidation enzyme of E. coli which depends on forming a complex with a subunit contributing enoyl‐CoA hydratase and alcohol dehydrogenase functionalities [36].…”
Section: Discussionmentioning
confidence: 99%
“…We are only aware of one other case of a Zn‐finger protein involved in a catalytic process, namely in adenylate kinase from Bacillus stearothermophilus (https://doi.org/10.2210/pdb1ZIN/pdb) where it provides a structural lid for the active site [35]. Another example where protein assembly is required to attain thiolase activity was reported for a trifunctional β‐oxidation enzyme of E. coli which depends on forming a complex with a subunit contributing enoyl‐CoA hydratase and alcohol dehydrogenase functionalities [36].…”
Section: Discussionmentioning
confidence: 99%
“…Three-dimensional structures have been obtained for bacterial and human TFE ( Figure 4 ) [ 23 , 24 , 25 ]. In addition, the structure of FadB from E. coli was published recently [ 26 ]. The FadBA complex is a hetero-tetramer composed of two copies of the 78 kDa multifunctional enzyme FadB, and two copies of the 42 kDa 3-ketoacyl-CoA thiolase FadA.…”
Section: Pathways Of Fatty Acid Degradationmentioning
confidence: 99%
“…Despite their homology, in vitro analysis suggested that FadIJ and FadBA complexes present many different features [ 26 , 59 ]. FadIJ was modeled as a hetero-octameric enzyme, possibly membrane-bound.…”
Section: Pathways Of Fatty Acid Degradationmentioning
confidence: 99%
“…Generally, the level of ATP is directly proportional to the intensity of the emitted light. By monitoring the level of ATP, the physiological and pathological properties of cells can be obtained [ 20 , 21 ]. In the area of bacteria detection, the ATP luminescent method can be used to measure the amount of bacteria conveniently and quickly.…”
Section: Introductionmentioning
confidence: 99%